KUALITAS REGULASI SEBAGAI PILAR UTAMA: MODERASI ATAS PERTUMBUHAN EKONOMI DALAM MENURUNKAN TINGKAT PENGANGGURAN DI ASEAN-6 - Nasrullah; Dedi Mardianto (CV. Adiba Aisha Amira, 2026)
Unemployment remains a major challenge to development in the ASEAN region, despite most countries recording positive economic growth. Differences in unemployment rates amidst relatively stable growth rates indicate the presence of structural factors that influence the ability of economic growth to create jobs. One key factor believed to play a strategic role is the quality of regulation, which determines market efficiency, the ease of doing business, and legal certainty for economic actors. Therefore, this study aims to analyse the role of regulatory quality as a key pillar that moderates the influence of economic growth on the reduction of unemployment rates in the ASEAN-6 countries (Indonesia, the Philippines, Vietnam, Thailand, Cambodia and Malaysia). This study employs a quantitative approach using panel data for the period 2004–2023. The sample was selected using a purposive approach, based on the criteria of being developing countries facing structural challenges in the labour market, a sufficiently significant variation in regulatory quality, and the availability of key variables sourced from the World Development Indicators. The data will be analysed using panel data regression with the Random Effect Model (REM), as well as Moderated Regression Analysis (MRA) interaction tests to identify the moderating role of regulatory quality. The results of the study indicate that economic growth significantly reduces the unemployment rate, and this effect is markedly reinforced by better regulatory quality. These findings underscore the importance of consistent regulatory reform to enhance the effectiveness of growth in creating jobs. Therefore, there is a need to simplify business procedures, improve transparency, and strengthen law enforcement in ASEAN countries.